Tissue specific profiling of females of Schistosoma japonicum by integrated laser microdissection microscopy and microarray analysis. - Geoffrey N Gobert (PLoS Neglected Tropical Diseases, 2009)
The functions of many schistosome gene products remain to be characterized. A major step towards elucidating function of these genes would be in defining their sites of expression. This goal is rendered difficult to achieve by the generally small size of the parasites and the lack of a body cavity, which precludes analysis of transcriptional profiles of the tissues in isolation.Here, we describe a combined laser microdissection microscopy (LMM) and microarray analysis approach to expedite tissue specific profiling and gene atlasing for tissues of adult female Schistosoma japonicum. This approach helps to solve the gene characterization "bottle-neck" brought about by acoelomy and the size of these parasites. Complementary RNA obtained after isolation from gastrodermis (parasite gut mucosa), vitelline glands and ovary by LMM were subjected to microarray analyses, resulting in identification of 147 genes upregulated in the gastrodermis, 4,149 genes in the ovary and 2,553 in the vitellaria.This work will help to shed light on the molecular pathobiology of this debilitating human parasite and aid in the discovery of new targets for the development of anti-schistosome vaccines and drugs.